On One Approach to Optimization of Recursive Function Computations - Ghazaryan, Artashes K. (Mathematical Problems of Computer Science, 2021)
The goal of this work is the theoretical justification and the development of a new optimizer that synthesizes programs calculating multivariate recursive functions and systems of functions. The current version of the optimizer processes a wide category of multivariate systems of recursive functions using two algorithms - stack recursion optimization and combined total replacement optimization. The results of this work can be used in development of packages, calculating the systems of recursive functions, modeling discrete multivariate systems with complex interconnections, solving boundary-value and field-value problems, etc.